Screening Strategies for COVID-19 in Patients With Hematologic Malignancies - Assi, Tarek; Samra, Bachar; Dercle, Laurent; Rassy, Elie; Kattan, Joseph; Ghosn, Marwan; Houot, Roch; Ammari, Samy (Frontiers in Oncology, 2020)
COVID-19 has been declared a pandemic by the world health organization. Patients with cancer, and particularly hematologic malignancies may be at higher risk for severe complications due to their malignancy, immune dysregulation, therapy, and associated comorbidities. The oncology community has been proactive in issuing practice guidelines to help optimize management, and limit infection risk and complications from SARS-COV-2. Although hematologic malignancies account for only 10% of all cancers, their management is particularly complex, especially in the time of COVID-19. Screening or early detection of COVID-19 are central for preventative/mitigation strategy, which is the best current strategy in our battle against COVID-19. Herein, we provide an overview of COVID-19 screening strategies and highlight the unique aspects of treating patients with hematologic malignancies.